Phenotype characteristic of colonic intraepithelial lymphocytes in patients with Crohn's disease - D. B. Nizheharodava; A. Ch. Shuleika; A. M. Starastsin; M. I. Vanslau; G. I. Ivanchyk; A. V. Vialichka; M. M. Zafranskaya (Медицинская иммунология, 2023)
Intraepithelial lymphocytes (IEL) play a critical role in maintaining the immune balance of the gut and provide the first line of mucosal defense against luminal antigens as well as rapidly respond to epithelial injury. Recently, IEL have received a lot of attention as key mediators of aberrant immune response resulted in persistent immune activation, inflammation and altered intestinal barrier function, seen in Crohn's disease (CD). This study describes for the first time subsets of colonic IEL in CD patients as compared to healthy controls aimed at characterization of altered IEL contribution to the pathogenesis of Crohn's disease.The peripheral venous blood and colon tissues were obtained from 10 CD patients and 6 donors. IEL were isolated from the mucosa by incubation the tissue in a predigesting solution. Lymphoid cells phenotype was investigated using monoclonal antibodies and flow cytometry.The majority of colonic IEL was identified as СD3+T lymphocytes and no significant differences were found in their numbers in investigated groups. However, changes in T cell subsets composition have been shown: the ratio of СD3+СD4+IEL and СD3+СD8+IEL was 1:1 in colon of CD patients and correlated with T cells in peripheral blood (R = 0.7; p < 0.05) while donor tissues were characterized by expected СD3+СD8+T killers prevalence and the ratio reached 1:2 (p < 0.05). The increase of unconventional γδIEL (mainly due to V81+T cells) and СD161+T cells in association with TNK cells decrease were revealed in colon (p < 0.01) as well as in peripheral blood (p < 0.05) of CD patients as compared to donors. Moreover, the number of colonic γδIEL was correlated with disease location (R = -0.6; p < 0.05), and disease behavior (R = 0.7; p < 0.01) according to Montreal classification.The observed data indicates changes in colonic IEL composition in CD patients that may provide valuable insight into the contribution of T helpers, γδT cells and mucosa-associated СD161+T cells in autoimmune intestinal inflammation but need further possible mechanisms discussion.